Cargo port choice equilibrium: The case of shipping lines and cargo port service providers. (August 2022) - Talley, Wayne K.; Ng, ManWo
Highlights: Shipping lines and providers of cargo port services do not choose their ports in isolation. To model interaction, a cargo port choice equilibrium model is proposed. Extends and unifies the shipping lines and cargo port service providers port choice literature. Equilibrium model can be used to forecast directional behavioral changes. Abstract: The cargo port choice literature has extensively investigated port choice from the shippers and shipping lines' perspective, and more recently, also from the perspective of cargo port service providers. This paper extends and unifies the shipping lines and cargo port service providers port choice literature by recognizing that shipping lines and providers of cargo port services do not choose their ports in isolation of each other. Instead, their choices are interdependent. To model this interaction, a cargo port choice equilibrium model is proposed. To demonstrate how the model can be used in practice, a discussion is provided of how the proposed equilibrium model can be adopted to forecast directional behavioral changes by carriers and cargo port service providers in the case of disturbances in the equilibrium.